Biomedical Optics 2008
DOI: 10.1364/biomed.2008.bsue11
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin adsorption to nanopatterned silicon surfaces

Abstract: The possibility of using surface topography for guidance of different biological molecules and cells is a relevant topic that can be applied to a wide research activity. This study investigated the adsorption of fibronectin to a diffraction grated silicon surface. The rectangular grating profile featured a controlled surface with 350 nm period and a corrugation depth of 90 nm. Results demonstrated that the controlled surface had a significantly positive effect on the fibronectin binding. Thus, nanoscale surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Protein adsorption facilitates the cellular interaction with the substrate surface. The number and strength of cells adhered to a substrate is inherently affected by the level of protein adsorption 26, 37–39. Surface topography has been shown to either directly influence the cell response, or indirectly affect the cell responses through the affects they have on the adsorption of proteins 10, 40–42.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Protein adsorption facilitates the cellular interaction with the substrate surface. The number and strength of cells adhered to a substrate is inherently affected by the level of protein adsorption 26, 37–39. Surface topography has been shown to either directly influence the cell response, or indirectly affect the cell responses through the affects they have on the adsorption of proteins 10, 40–42.…”
Section: Discussionmentioning
confidence: 99%
“…The number and strength of cells adhered to a substrate is inherently affected by the level of protein adsorption. 26,[37][38][39] Surface topography has been shown to either directly influence the cell response, or indirectly affect the cell responses through the affects they have on the adsorption of proteins. 10,[40][41][42] Cell adhesion results comparing substrates coated with fibronectin, collagen, or no protein revealed that on all protein-coated substrates, there was significantly more cell adhesion on both of the protein-coated substrates compared with the substrates without any protein coating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein adsorption facilitates the cellular interaction with the substrate surface. The number and strength of cells adhered to a substrate is inherently affected by the level of protein adsorption 30, 36, 37. Our results found the fewest number of astrocytes on PMMA compared to any other surface, which could be explained by a low amount of protein adsorption on PMMA.…”
Section: Discussionmentioning
confidence: 99%
“…During recent years, this field is rapidly expanding. One of the new subfields here includes studies of protein adsorption on rough surfaces with well controlled nanoroughness, e.g., on surfaces obtained by using e-gun evaporation at an oblique angle of incidence between the substrate and the incoming flux [4][5][6] or on diffraction-grated surfaces [7]. Another subfield encompasses studies of protein adsorption and DNA hybridization on supported nanoparticles (see, e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%